Pretreatment of Aloe Vera and Its Effect on the Properties of Flour and Vermicelli Produced - Nova Ellya Widiyati; Iffah Muflihati; Rini Umiyati; Arief Rakhman Affandi (Jurnal Sains dan Terapan Kimia, 2023)
Aloe vera powder has a less bright color due to the browning reaction. Pretreatment was carried out to improve the quality of aloe vera flour. Aloe vera flour can be used to manufacture food products, one of which is vermicelli. This study aimed to determine the effect of different pretreatments, namely blanching, sodium metabisulfite immersion, sodium bisulfite immersion, and steam blanching, on the characteristics of aloe vera flour and its application to vermicelli. The research steps included aloe vera pretreatment and aloe vera flour production, vermicelli production with aloe vera flour substitution, and analysis. The results showed that the pretreatment produced aloe vera and vermicelli flour with a brighter color. Pretreatment also affects water content, water-holding capacity, oil-holding capacity, and cooking properties. But the pretreatment did not affect the sensory properties of vermicelli.